Alterations of Eye Movement Control in Neurodegenerative Movement Disorders. (18th May 2014) - Gorges, Martin; Pinkhardt, Elmar H.; Kassubek, Jan
Abstract : The evolution of the fovea centralis, the most central part of the retina and the area of the highest visual accuracy, requires humans to shift their gaze rapidly (saccades) to bring some object of interest within the visual field onto the fovea. In addition, humans are equipped with the ability to rotate the eye ball continuously in a highly predicting manner (smooth pursuit) to hold a moving target steadily upon the retina. The functional deficits in neurodegenerative movement disorders (e.g., Parkinsonian syndromes) involve the basal ganglia that are critical in all aspects of movement control. Moreover, neocortical structures, the cerebellum, and the midbrain may become affected by the pathological process. A broad spectrum of eye movement alterations may result, comprising smooth pursuit disturbance (e.g., interrupting saccades), saccadic dysfunction (e.g., hypometric saccades), and abnormal attempted fixation (e.g., pathological nystagmus and square wave jerks). On clinical grounds, videooculography is a sensitive noninvasive in vivo technique to classify oculomotion function alterations. Eye movements are a valuable window into the integrity of central nervous system structures and their changes in defined neurodegenerative conditions, that is, the oculomotor nuclei in the brainstem together with their directly activating supranuclear centers and the basal ganglia as well as cortical areas of higher cognitive control of attention.